The Relations between the Komitopules and the Peoples of the Steppes of Eastern Europe. A Vain Hope for an Alliance - Dudek, Jarosław (Studia Ceranea, 2025)
Medieval Bulgaria maintained relations with the Pontic nomadic communities. The times of the rule of the Komitopules were not exceptional in this respect. In the face of a difficult war with Byzantium, the Hungarians and Pechenegs could prove to be valuable allies. Relations with the former deteriorated during the construction of the feudal kingdom of the Arpads, associated with Latin Christianity. Only John Skylitzes writes about the would-be alliance of the Bulgarians with the Pecheneg tribes. It was supposed to take place in 1017, but the Pechenegs gave up supporting the Bulgarians. The reason could have been the actions of the Byzantines, who, by intervening in Black Sea Khazaria or exerting diplomatic pressure, could have persuaded the Pechenegs to withdraw. It cannot be ruled out that the Pechenegs were threatened by Rus’ or actions taken by Bolesław I the Brave, who after the mission of St. Bruno entered into closer relations with the Pechenegs. After all, Bulgaria after 1017 could not count on the support of potential northern allies.